PENGARUH RED FLAGS, SKEPTISME PROFESIONAL AUDITOR, KOMPETENSI, INDEPENDENSI, DAN PROFESIONALISME TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI PEKANBARU, PADANG, DAN MEDAN YANG TERDAFTAR DI IAPI 2013) - Sandi Prasetyo; Kamaliah -; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Fraud and error is very different, which sets it apart is the underlying action, whether the act was committed intentionally or not. If the act was committed intentionally, then it is called fraud (fraud) and when the act was committed by accident, then it is called by mistake (error). The purpose of this study is to look at the effect of red flags, the auditor's professional skepticism, competence, independence, and professionalism to the auditor's ability to detect fraud. This research was conducted auditor in KAP in the Pekanbaru, Padang, and Medan. From the test results it is known that the red flags, the auditor's professional skepticism, competence, and professionalism affect the auditor's ability to detect fraud. While not affect the independence of the auditor's ability to detect fraud.Keywords: Red Flags, Auditor Professional Skepticism, Competence, Independence, professionalism and ability Auditor in Detecting Fraud.